Beyond The Outbreak: A Review Of Bigdata Analytics In Proactive Infectious Diseaseprevention For Risk Mitigation For Covid‑19 - Nurun Nuha; Sakinah Ali Pitchay; Azni Hazlizan Ab Halim; Murtadha Arif Bin Sahbudin; Ilfita Sahbudin (Springer Nature, 2025)
Indexed by WOS